Biogeographical Landscape of the Human Face Skin Microbiome Viewed in High Definition - Michael Brandwein (Society for Publication of Acta Dermato-Venereologica, 2021)
The bacterial community that colonizes the human face imparts physiochemical and physiological effects on the facial skin. These skin-microbe interactions impact dermatological, cosmetic and skincare applications due to the centrality of the human face in daily interactions. However, fine-scale characterization of the human face skin microbiome is lacking. Using 16S rRNA sequencing and 3D cartography, this study plotted and characterized the facial skin microbiome in high- definition, based on 1,649 samples from 12 individuals. Analysis yielded a number of novel insights, including that of the relative uniformity of skin microbiome composition within skin sites, site localization of certain microbes, and the interpersonal variability of the skin microbiome. The results show that high-resolution topographical mapping of the skin microbiome is a powerful tool for studying the human skin microbiome. Despite a decade of skin microbiome research, there is still much to be discovered.